2014
DOI: 10.1249/mss.0000000000000177
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Disturbed Sleep and Increased Illness in Overreached Endurance Athletes

Abstract: This study confirms sleep disturbances and increased illness in endurance athletes who present with symptoms of F-OR during periods of high volume training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
158
2
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(198 citation statements)
references
References 34 publications
(40 reference statements)
17
158
2
5
Order By: Relevance
“…7 Collectively, the data presented in the current study provide evidence for the association between heightened internal-TL and the presence of self-reported illness. Whilst these data support previous research of the increased risk of illness associated with heightened training, 22,27,28 the results of the present study are specific to the athletic cohort recruited. Further, it must be noted that these findings are applicable to other team-sport athletes, however the training load values will vary depending on the typical training undergone by the athletes.…”
Section: Discussionsupporting
confidence: 90%
“…7 Collectively, the data presented in the current study provide evidence for the association between heightened internal-TL and the presence of self-reported illness. Whilst these data support previous research of the increased risk of illness associated with heightened training, 22,27,28 the results of the present study are specific to the athletic cohort recruited. Further, it must be noted that these findings are applicable to other team-sport athletes, however the training load values will vary depending on the typical training undergone by the athletes.…”
Section: Discussionsupporting
confidence: 90%
“…These findings contradict the theory that sleep is proportional to restorative needs and instead fall in line with results from similar studies that have reported impaired sleep efficiency during periods of intense training (Fietze et al, 2009) or when athletes have become overreached (Hausswirth et al, 2014). However, it is interesting to note that actual sleep time was significantly higher during IT in CON than HCHO, which may indicate an increased requirement for recovery and/or expression of fatigue.…”
Section: Discussioncontrasting
confidence: 72%
“…Previous sleep research has primarily focused on physically active groups of 'good sleepers' whereby the exercise stress is low and the margin for sleep improvement is relatively small (ceiling effect) (Driver & Taylor, 2000). A small collection of studies have reported sleeping behaviours in athletes, finding evidence for sleep disturbance during busy times in the season (Taylor et al, 1997) and reduced sleep efficiency, duration and immobile time when diagnosed as overreached (Hausswirth et al, 2014). Conversely, increases in slow wave sleep during busy periods have been reported, suggesting improved sleep quality and thereby supporting the restorative theory of sleep (Oswald, 1970).…”
Section: Introductionmentioning
confidence: 99%
“…During recovery from a soccer match, soccer players are prone to delayed onset muscle soreness [79] that may induce difficulties remaining immobile during sleep and thus impairing sleep quantity and quality [80]. Non-steroidal antiinflammatory drug consumption may consequently influence overall sleep by mediating exercise-induced muscle soreness.…”
Section: Caffeine Alcohol Medication and Sleepmentioning
confidence: 99%